Assessing non-aggressiveness of untreated, local and regional, papillary thyroid cancer. (June 2020) - van Gerwen, Maaike; Alpert, Naomi; Sinclair, Catherine; Kale, Minal; Genden, Eric; Taioli, Emanuela
Highlights: Local stage, papillary thyroid cancer shows high rates of non-aggressiveness. High rates of non-aggressiveness are found in tumors up to 2 cm. Even regional cancer in patients below 40 years has high rate of non-aggressiveness. Active surveillance may be appropriate for small, local, papillary thyroid cancer. Abstract: Objectives: With a steadily increasing thyroid cancer incidence, information regarding cancer aggressiveness is essential to determine which patients may be suitable for active surveillance. This study assessed the extent of non-aggressiveness of untreated, local and regional stage, papillary thyroid cancer. Materials and methods: We used the Surveillance, Epidemiology, and End Results (SEER) registry and included 1423 local stage and 337 regional stage papillary thyroid cancer cases. Thyroid cancer specific survival was estimated conditional on the absence of death due to competing causes using competing risk methods. Stratified analyses were done to determine non-aggressiveness among different patient and tumor characteristics. Results: The overall rate of non-aggressiveness for local stage thyroid cancer was 99.34% (95% CI: 99.33–99.35%), with a rate of non-aggressiveness of 98.85% (95% CI: 98.77–98.93%) for males and 99.48% (95% CI: 99.46–99.49%) for females (p = 0.055). Rate of non-aggressiveness was significantly lower in patients >60 years compared to patients ≤60 years (p < 0.001). Although the rate of non-aggressiveness was the same for tumors ≤10 mm and tumors of 11–20 mm, tumors measuring >20 mm had a significantly lower rate of non-aggressiveness (p = 0.002). The overall rate of non-aggressiveness for regional stage thyroid cancer was 72.58% (95% CI: 70.61–74.56%). Conclusion: We found high rates of non-aggressiveness in untreated, local stage, papillary thyroid cancer, particularly in younger patients with small (≤2 cm) thyroid cancer, suggesting that these patients may be good candidates for active surveillance.